CONCEPT, POSSIBILITIES AND LIMITATIONS OF SYNERGETIC METHOD IN COMPANY MANAGEMENT - Mikhail B. Flek; Yulia K. Verchenko (Advanced Engineering Research)
The matter and basic features of the synergetic method as a vitality saving tool with the simultaneous search of new development alternatives in the behavioral research on complex systems are considered.